PENGARUH GAYA KEPEMIMPINAN DAN KECERDASAN EMOSIONAL TERHADAP KINERJA PERSONEL KEPOLISIAN RESORT (POLRES) SAMPANG YANG DIMEDIASI OLEH DISIPLIN KERJA - Dwi Abdillah (Program Pascasarjana Universitas Wijaya Putra Surabaya, 2023)
This study was to analyze the effect of leadership style and emotional intelligence on the performance of the Sampang Resort Police personnel mediated by work discipline. The results of the study show that leadership style has a positive and significant effect on employee performance. This is evidenced by the original sample value of 0.351 and a p value of 0.000. Leadership style has a positive and significant effect on work discipline. This is evidenced by the original sample value of 0.491 and a p value of 0.000. Emotional intelligence has a positive and significant effect on work discipline. This is evidenced by the original sample value of 0.256 and a p-value of 0.000. Emotional intelligence has no significant positive effect on performance. This is evidenced by the original sample value of 0.148 and a p value of 0.000. Work discipline has a positive and significant effect on employee performance. This is evidenced by the original sample value of 0.345 and a p value of 0.004. Leadership style has no significant positive effect on performance mediated by work discipline. This is evidenced by the original sample value of 0.169 and a p value of 0.000. Emotional intelligence has no significant positive effect on employee performance mediated by work discipline. This is evidenced by the original sample value of 0.088 and a p value of 0.000.